2011
DOI: 10.1007/s00540-011-1196-2
|View full text |Cite
|
Sign up to set email alerts
|

Backboard insertion in the operating table increases chest compression depth: a manikin study

Abstract: The quality of chest compression (CC) is influenced by the surface supporting the patient. The present study compared chest compression depth with and without a rigid backboard on an operating table with a pressure-distributing mattress. We hypothesized that the presence of a backboard would result in an increased depth of chest compression on the operating table with a pressure-distributing mattress. In a randomized crossover trial, we simulated in-hospital cardiac arrest in a Resusci Anne SkillReporter model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 11 publications
0
20
1
2
Order By: Relevance
“…A similar result was reported when CC were performed on a CPR manikin on a firm operating room bed with a pressure reduction mattress added on top. 17 Our study was different from those studies, quantifying mattress displacement during CCs coached to the deeper 2010 Guideline depth (>50 mm). This suggests that use of an externally placed sternal accelerometer device could potentially underestimate actual sternum-to-spine CC depth and potentially misguide rescuers to achieve shallower CC depth.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…A similar result was reported when CC were performed on a CPR manikin on a firm operating room bed with a pressure reduction mattress added on top. 17 Our study was different from those studies, quantifying mattress displacement during CCs coached to the deeper 2010 Guideline depth (>50 mm). This suggests that use of an externally placed sternal accelerometer device could potentially underestimate actual sternum-to-spine CC depth and potentially misguide rescuers to achieve shallower CC depth.…”
Section: Discussioncontrasting
confidence: 63%
“…7 However, very few studies evaluate the effectiveness of the backboard directly, and the results are inconclusive. 1017 An important reason the prior results are inconclusive is that the quality of CC is often not optimized in these experiments. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Backboards are commonly used to achieve target depths [107][108][109] and reduce rescuer exertion, 110 but their placement interrupts CPR. 111 For this reason, the expert panel recommends placement of a backboard or firm, hard surface as soon as possible and in coordination with other mandatory pauses in compressions to minimize interruption time.…”
Section: Ensure a Firm Hard Surfacementioning
confidence: 99%
“…[13][14][15] To prevent the adverse effects of a hospital-bed mattress on CC, the use of a backboard, mattress compression cover and vacuum pump has been studied. 16,17 However, Nishisaki et al 18 suggested that a backboard should be used for CPR only in paediatric beds and soft beds of the intensive care unit, whereas other studies reported that the firmness of the surface had no significant effect on CPR. 5,6 In our study, there were no significant differences in CC depth between the flat floor and the three types of home-bed mattresses.…”
Section: Discussionmentioning
confidence: 99%